DEVELOPMENT OF A DEEP LEARNING-BASED CHARACTER BULDING AFFIRMATION MODEL IN INDONESIAN LANGUAGE LEARNING IN JUNIOR HIGH SCHOOL - M. Agus (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
This study aims to develop a character building affirmation learning model based on a deep learning approach in the context of Indonesian language learning at the Junior High School (SMP) level. This approach emphasizes strengthening conceptual understanding and internalization of character values ​​through reflective, collaborative, and meaningful learning activities. The study used the Design and Development Research (DDR) method with a 4D development model: Define, Design, Develop, and Disseminate. The research subjects consisted of grade VIII students and Indonesian language teachers at SMP. Data collection techniques included observation, interviews, documentation, expert validation, and questionnaires to students and teachers. The validation results by three experts—character education, educational technology, and Indonesian language teachers—showed that this model is very valid, with an average score of 90% in the content, construct, and technology aspects. A limited trial conducted on 30 grade VIII students showed that 87% of students felt that this model made it easier for them to understand character values ​​in depth. In addition, teachers considered this model practical, interactive, and able to increase students' active involvement in the learning process. These findings indicate that the affirmation character building model based on deep learning is not only effective in building attitude competencies and understanding of values, but is also relevant to be applied in Indonesian language learning. This model has the potential to be an innovative approach in technology-based character education that supports pedagogical transformation at the junior high school level